New LMI-Based Conditions on Neural Networks of Neutral Type with Discrete Interval Delays and General Activation Functions - Guoquan Liu; Shumin Zhou; He Huang (Abstract and Applied Analysis)
The stability analysis of global asymptotic stability of neural networks of neutral type with both discrete interval delays and general activation functions is discussed. New delay-dependent conditions are obtained by using more general Lyapunov-Krasovskii functionals. Meanwhile, these conditions are expressed in terms of a linear matrix inequality (LMI) and can be verified using the MATLAB LMI toolbox. Numerical examples are used to illustrate the effectiveness of the proposed approach.